Precompactness of Isometric Conjugacy Classes of Continuous Maps - Dong, Meihua; Morales, Carlos (Topology Proceedings, 2020)
Let C be the set of isometric conjugacy classes of continuous maps of compact metric spaces equipped with the quasimetric de fined by Alexander Arbieto and Carlos Arnoldo Morales Rojas, [Topological stability from Gromov-Hausdorff viewpoint, Discrete Contin. Dyn. Syst. 37 (2017), no. 7, 35313544]. We prove that a subset of C is precompact if and only if it is equicontinuous.